Cloud computing: cloud adoption in professional practice - Nazri, Nadhirah; Ibrahim, Jamaludin (International Journal of Science and Research, 2015)
Cloud computing creates new opportunities in the era of technological advancement specifically to Malaysia. This paper will present and discuss an overview of cloud computing and how the implementation of cloud computing impact an organization and an industries. There are many sectors can get the benefits when adopting the cloud computing services, including education, healthcare, agriculture, tourism, banking, and the automotive industry. In the paper, we briefly highlight certain industry which cloud adoption can significantly enhance system efficiency, effectiveness, and reliability.